2013
DOI: 10.4103/0974-8520.123117
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Yoga for sustained attention in university students

Abstract: Sustained attention (SA) is a vital function mediated by the right frontal - parietal cortex. The digit vigilance test (DVT) measures SA. Assessment of SA in students for their academic excellence is considered to be an essential part of a neuropsychological evaluation. The objective of this study is to determine SA in students undergoing training of integrated Yoga module (IYM). A total of 66 university students aged between 18-37 years participated in this study with a single group pre-post design. The DVT d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Yoga breathing has been found to improve attention based on a digit vigilance task (Cohen’s=0.61) [11] and reduce reaction time (Cohen’s d=0.404) [16]. The yoga breathing practices differed, since in some practices the emphasis was on increasing the rate [17], while in others the emphasis was on the depth of breathing [18].…”
Section: Discussionmentioning
confidence: 99%
“…Yoga breathing has been found to improve attention based on a digit vigilance task (Cohen’s=0.61) [11] and reduce reaction time (Cohen’s d=0.404) [16]. The yoga breathing practices differed, since in some practices the emphasis was on increasing the rate [17], while in others the emphasis was on the depth of breathing [18].…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that Suryanamaskara, a yogic practice was effective in leading to relaxation dispositions such as physical relaxation, mental quiet, at ease/peace, rested and refreshed, strength and awareness and joy and reduces sleepiness, somatic stress, worry and negative emotion at a dispositional level. [ 18 ] Yogic practices play an important role in enhancing emotional sensitivity,[ 19 ] sustained attention,[ 20 ] mental performance,[ 21 ] and balance personality trait[ 22 ] among students, thus paving the way for their academic excellence. Yoga also reduces perceived stress and negative affects in college students thereby improving psychological well-being in them.…”
Section: Yogamentioning
confidence: 99%
“…This is an open-access article distributed under the terms of the Creative Commons Attribution-NonCommercial 4.0 International License (http://creativecommons.org/licenses/by-nc/4.0/) which permits copy and redistribute the material just in noncommercial usages, provided the original work is properly cited. associated with task difficulty or complexity (6).…”
Section: Introductionmentioning
confidence: 99%